April global radiation in relation to subsequent monsoon rainfall in India - SEN, P. N.; RAMACHANDRAN , G.; BANERJEE, A. K. (MAUSAM, 2022)
Monthly mean global radiation charts for the months March to Mayare examined year by year for the period 1960 to 1975 in relation to the behaviour of the subsequent monsoon rainfall in the country. April charts show a region of high radiation extending from Rajasthan to Tamil Nadu through the Deccan plateau in the years when the subsequent monsoon rainfall is normal over the country. In deficient years, viz., 1965, 1966 and 1972 the pattern changes substantially; a tongue of low radiation appears over the Peninsula and the Central parts of India. No such change in the radiation paltem is observed in the preceding and the succeeding months (,iz., March and May). However, similar pattern is observed in April 1970 also although this was a good monsoon year. In this connection, five-day mean radiation charts for the years 1970 (normal monsoon) and 1972 (drought year) have also been examined. It has been found that in 1970, the region of high radiation appean over Deccan plateau during the last two pentads of April while this feature is not seen in 1972. April mean radiation chart may, therefore, serve as a clue for predicting the behaviour of the subsequent mosoon rainfall in the country.